Polymer‐Coated Urea Improved Corn Response Compared to Urea‐Ammonium‐Nitrate When Applied on a Coarse‐Textured Soil. (1st March 2016) - Maharjan, Bijesh; Ferguson, Richard B.; Slater, Glen P.
Abstract : Increasing economic and environmental concerns in corn ( Zea mays L.) production have prompted the need for improved N management. In this study, effects of two N sources [urea‐ammonium‐nitrate (UAN) and polymer‐coated urea (PCU)] on corn response were evaluated at different N rates over three site‐years. An additional N treatment of split‐applied UAN (UAN‐SP) based on the University of Nebraska‐Lincoln recommendation algorithm was also included. Leaf chlorophyll was indirectly measured using a chlorophyll meter at different corn growth stages for all N treatments to determine in‐season corn N status. Both PCU and UAN‐SP increased grain yield compared to UAN, even when the UAN rate was higher than that of PCU or UAN‐SP. The PCU treatment applied at 168 kg N ha −1 was as effective as UAN‐SP applied at ∼200 kg N ha −1 . At early growth stages, leaf chlorophyll was higher in a dry year than in wet years, when more N loss was likely. At different growth stages taken individually or together, chlorophyll meter readings were significantly correlated to grain yield. Temporal N release from PCU in the conditions of this study was not an issue, as shown by the consistently greater chlorophyll meter readings in PCU treatments than in UAN treatments, regardless of interannual climatic variations. These results indicate that PCU consistently performed better than UAN.